THE EFFECT OF ENGLISH LITERATURE ON INTERCULTURAL AWARENESS AMONG UZBEK STUDENTS - Zokirova Marjona Xislatjon qizi, (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Annotation : This paper explores the impact of English literature on developing intercultural awareness among Uzbek students. Through the analysis of literary texts such as novels, short stories, and poems by English-speaking authors, the study investigates how exposure to diverse cultural themes, values, and perspectives enhances students' understanding of other cultures. The research is based on classroom observations, student surveys, and interviews conducted at selected universities in Uzbekistan. Findings indicate that the study of English literature not only improves language proficiency but also fosters empathy, tolerance, and critical thinking, thereby playing a crucial role in shaping globally minded individuals.